2024
DOI: 10.3201/eid3002.231274
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Spread of Highly Pathogenic Avian Influenza A(H5N1) Clade 2.3.4.4b Virus in Wild Birds, South Korea, 2022–2023

Ye-Ram Seo,
Andrew Y. Cho,
Young-Jae Si
et al.

Abstract: During October 2022–March 2023, highly pathogenic avian influenza (HPAI) A(H5N1) clade 2.3.4.4b virus caused outbreaks in South Korea, including 174 cases in wild birds. To understand the origin and role of wild birds in the evolution and spread of HPAI viruses, we sequenced 113 HPAI isolates from wild birds and performed phylogenetic analysis. We identified 16 different genotypes, indicating extensive genetic reassortment with viruses in wild birds. Phylodynamic analysis showed that the viruses were most like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…South Korea has experienced continual outbreaks of HPAI since 2003, and since 2020, these outbreaks have caused significant socio-economic losses during four consecutive winter seasons (2020-2024) [13]. Previous studies suggested that the incursion of HPAI viruses into East Asia is predominantly attributed to viral strains originating from breeding grounds in Eurasia [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…South Korea has experienced continual outbreaks of HPAI since 2003, and since 2020, these outbreaks have caused significant socio-economic losses during four consecutive winter seasons (2020-2024) [13]. Previous studies suggested that the incursion of HPAI viruses into East Asia is predominantly attributed to viral strains originating from breeding grounds in Eurasia [15].…”
Section: Resultsmentioning
confidence: 99%
“…In Korea, HPAI viruses, especially H5Nx viruses from various clades of the Goose/ Guangdong lineage, have been seasonally detected in poultry since 2003 [13]. It has been suggested that viral reassortment occurs at breeding sites in Siberia, and that these newly generated variants are introduced into East Asia, including Korea, during the winter migration of wild birds [14].…”
Section: Introductionmentioning
confidence: 99%
“…The number of genotypes in Japan in 2022–2023 was the highest since the initial outbreak of the Gs/Gd virus in 2004 ( Mase et al, 2005 ), and higher than the five genotypes identified in 2020–2021 and 2016–2017 ( Mine et al, 2022 , Takemae et al, 2017 ). Recently, multiple HPAIVs with different gene constellations have been isolated in Asian countries (e.g., China in 2021–2022 ( Yang et al, 2023 ) and Korea in 2022–2023 ( Kang et al, 2023 , Lee et al, 2023 , Seo et al, 2024 )). H5 HPAIVs of multiple genotypes (more than 60 genotypes since 2020 and 16 genotypes in 2022–2023) have also been detected in Europe ( European Food Safety Authority 2023a ).…”
Section: Resultsmentioning
confidence: 99%
“…In South Korea, the H5N1 2.3.4.4b HPAI virus caused multiple outbreaks in wild birds and poultry from October 2022 to its eradication in March 2023, with 75 cases in poultry farms and 174 cases in wild birds reported ( 8 ). Until this report, the H5N1 2.3.4.4b HPAI virus responsible for the outbreaks in South Korea had not been detected in birds since April 2023, despite large-scale active surveillance targeting both wild birds and poultry.…”
Section: Introductionmentioning
confidence: 99%